36.9k views
1 vote
If f(x) = 3x+ 10x and g(x) = 4x - 2, find (f - g)(x).

2 Answers

7 votes

Answer:

-x + 12

Explanation:

Shown in picture:

If f(x) = 3x+ 10x and g(x) = 4x - 2, find (f - g)(x).-example-1
User Antiarchitect
by
5.4k points
3 votes

Answer:

9x +2

Explanation:

f(x) = 3x+ 10x

g(x) = 4x - 2,

(f - g)(x)= 3x+10x - (4x-2)

Distribute the minus sign

= 3x+10x -4x+2

Combine like terms

= 9x +2

User Deemer
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.